Tinjauan Fenomena Kerusakan Lingkungan Dampak Alih Fungsi Lahan Mangrove (Studi Kasus Desa Tapak Kuda, Kecamatan Tanjung Pura, Kabupaten Langkat, Sumatera Utara) - A. Hadian Pratama Hamzah; Cicik Suriani; Puji Prastowo; Sohifah Sohifah; Nurhasanah Nurhasanah (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to analyze the impact of mangrove land conversion on the social life of the community and describe the form of sustainable mangrove area management in Tapak Kuda Village, Tanjung Pura District, Langkat Regency. The research method used is a mixed research method. A mixed research method is a research method that combines or associates quantitative and qualitative methods. The results of the study indicate that the social impact of mangrove land conversion results in changes in the social conditions of the community based on employment opportunities of 66.36% in the high category. Based on the income level of 83.13% which means high. Based on the level of education 69.46% in the high category, meaning that it illustrates that the state of education in this village is still low. Based on the pattern of ownership and use of natural resources 53.50% of the answer category is not high. Based on the condition of natural resource use 45.52% in the high category. The process of implementing community-based mangrove forest management in Tapak Kuda Village, Tanjung Pura District, Langkat Regency consists of several stages as follows: a) Planning stage; b) Implementation stage; c) Maintenance stage; and d) Monitoring stage. In conclusion, the conversion of mangrove land has an impact on the social life of the community in Tapak Kuda Village, Tanjung Pura District, Langkat Regency.   Keywords: Impact, Conversion of Function, Mangrove Land, Social Conditions of the Community, Environmental Costal Management.